Accounting and social capital: A review and reflections on future research opportunities. (14th April 2022) - de Villiers, Charl; La Torre, Matteo; Botes, Vida
Abstract: We explore how the concept of social capital is used and theorised in accounting research by performing a structured literature review, and a critical analysis, of articles published in leading accounting journals. We identify two research paths, namely (1) how social capital influences accounting, and (2) how accounting influences social capital formation. We highlight that both accounting and social capital emanate from the social connections between individuals. We conclude that, although social capital is important in accounting, it is still under‐researched. This provides research opportunities for theory development, and interdisciplinary perspectives. We offer several further suggestions for future research.